Civil Society of East Java Humanitarian Network (JKJT) "Street Children's Assistance with NGOs" - Faradila, Rifka; Ramdani, Rachmat; Nababan, Rudyk (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This journal aims to determine the strengthening of civil society in an NGO organization engaged in the social sector. As a form of concern for the fate of street children who are also children of the nation who are entitled to a decent life. Street children assistance seeks to eradicate street children from the streets and make them independent and have human dignity. The assistance for street children carried out by JKJT includes outreach to street children, the process of assisting street children, approaches used in assisting street children, motivational activities given to street children and the results of this assistance.